Correlation Between Democratization and GDP Growth in the Western Balkans Countries - Mancheva, Galya (Research Papers, 2021)
The present study aims at tracing the correlations between democratization and GDP growth in the Western Balkans for the period 2009-2018. To achieve this goal, a democratization index is used, which refers to GDP growth through a Pearson bilateral correlation. This methodology provides an opportunity to track whether (1) there is a statistically significant linear relationship between two continuous random variables – democratization index and GDP growth, (2) the strength of the linear relationship between them and (3) its direction. The study takes into account the countries of the Republic of Albania, the Republic of Serbia, the Republic of Northern Macedonia, Montenegro and the Federation of Bosnia and Herzegovina. As a result of the analysis, it was found that with regard to these countries, the processes of democratization do not lead to economic growth. An exception to this conclusion is the Federation of Bosnia and Herzegovina, where GDP growth is a consequence of democratization and therefore only in this country does democratization lead to economic growth.
Keywords: Democratization; GDP growth; Pearson correlation; Western balkans; GDP